Incubating parents serve as visual cues to predators in Kentish plover (Charadrius alexandrinus). - Noémie Engel; Zsolt Végvári; Romy Rice; Vojtěch Kubelka; Tamás Székely (PLoS ONE, 2020)
Ground-nesting birds face many challenges to reproduce successfully, with nest predation being the main cause of reproductive failure. Visual predators such as corvids and egg-eating raptors, are among the most common causes of nest failure; thus, parental strategies that reduce the risk of visual nest predation should be favored by selection. To date, most research has focused on egg crypsis without considering adult crypsis, although in natural circumstances the eggs are covered by an incubating parent most of the time. Here we use a ground-nesting shorebird, the Kentish plover (Charadrius alexandrinus) as model species to experimentally test whether decoy parents influence nest predation. Using artificial nests with a male decoy, a female decoy or no decoy, we found that the presence of a decoy increased nest predation (N = 107 nests, p < 0.001). However, no difference was found in predation rates between nests with a male versus female decoy (p > 0.05). Additionally, we found that nests in densely vegetated habitats experienced higher survival compared to nests placed in sparsely vegetated habitats. Nest camera images, predator tracks and marks left on eggs identified the brown-necked raven (Corvus ruficollis) as the main visual nest predator. Our study suggests that the presence of incubating parents may enhance nest detectability to visual predators. However, parents may reduce the predation risk by placing a nest in sites where they are covered by vegetation. Our findings highlight the importance of nest site selection not only regarding egg crypsis but also considering incubating adult camouflage.